2019
DOI: 10.3390/app9163395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of High-Speed Handpiece Cutting Efficiency According to Bur Eccentricity: An In Vitro Study

Abstract: This study aimed to evaluate the correlation between the cutting efficiency and bur eccentricity of high-speed handpieces. The prepared lithium disilicate samples were digitized using a 3D model scanner (reference model, RM) (n = 45), and the lithium disilicate samples were cut using three high-speed handpieces. To evaluate the cutting efficiency, the cut lithium disilicate sample was digitized (cutting model, CM), and the RM and CM were superimposed using a 3D analysis software. Bur eccentricity of the high-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…The learning effect (reduction in working time) according to repeated learning with the intraoral scanner has been confirmed in previous studies [ 26 , 27 , 28 ]. Similarly, in the present study, a significant decrease in the working time was observed with repetition of the intraoral scanning task ( p < 0.001).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The learning effect (reduction in working time) according to repeated learning with the intraoral scanner has been confirmed in previous studies [ 26 , 27 , 28 ]. Similarly, in the present study, a significant decrease in the working time was observed with repetition of the intraoral scanning task ( p < 0.001).…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, high muscle activation was observed in the shoulder muscle (T) during the intraoral scanning task and in the two arm muscles (EDC and FDS) and in the shoulder muscle (T) in the tooth preparation task ( Table 1 ). A previous study reported that a force of 0.9 N or more is applied to the teeth during tooth preparation for a desired shape [ 28 ]. Therefore, it can be inferred that the high activation of the arm muscles (EDC and FDS) during the tooth preparation task in the present study was because of gripping the dental ultra-fast handpiece and pressing it against the teeth ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean clinical force applied to the DATH with a bur in the chuck was reported as 99.3 g, substantiating the range 50–150-g range [ 2 ]. A high-speed handpiece with cutting efficiency according to the bur eccentricity with a constant weight load of 0.9 N for 15 s was also studied in [ 3 ]. An experimental custom-made device was used to hold the high-speed handpiece and specimen in their cutting test.…”
Section: Introductionmentioning
confidence: 99%